2020
DOI: 10.1080/08897077.2019.1671935
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Coverage and Utilization of Nicotine Patches after Receipt of a Prescription

Abstract: Introduction: Changes in reimbursement policy have made nicotine replacement therapy (NRT) much more available, but little is known about what happens to patients after they receive their prescription. This study describes rates of successfully filling prescriptions for NRT and its association with type of insurance. Methods: We identified 224 patients who received a prescription for NRT during an outpatient visit to an academic medical center between January 1st 2016 and February 10th 2017. We conducted tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The authors acknowledge the inability of their study design to attribute causality and the inability to adjust for potential time‐varying confounders. In addition, it cannot be assumed that the smoking cessation medication prescribed was actually picked up from a pharmacy and used by the consumer, given that past studies have found that 20% of people prescribed NRT do not try to fill it [7]. Other limitations to note include the potential for Type 1 error (given multiple tests of significance), and the large effect sizes and extremely wide confidence intervals observed for the analysis exploring the impact of varenicline prescribing on ‘suicide deaths’ (suggestive of a sparse data issue and thus probably a spurious finding).…”
mentioning
confidence: 99%
“…The authors acknowledge the inability of their study design to attribute causality and the inability to adjust for potential time‐varying confounders. In addition, it cannot be assumed that the smoking cessation medication prescribed was actually picked up from a pharmacy and used by the consumer, given that past studies have found that 20% of people prescribed NRT do not try to fill it [7]. Other limitations to note include the potential for Type 1 error (given multiple tests of significance), and the large effect sizes and extremely wide confidence intervals observed for the analysis exploring the impact of varenicline prescribing on ‘suicide deaths’ (suggestive of a sparse data issue and thus probably a spurious finding).…”
mentioning
confidence: 99%